2023
DOI: 10.1002/epi4.12830
|View full text |Cite
|
Sign up to set email alerts
|

Cenobamate in refractory epilepsy: Overview of treatment options and practical considerations

Bettina Schmitz,
Simona Lattanzi,
Kristl Vonck
et al.

Abstract: Management of drug resistant epilepsy (DRE) represents a challenge to the treating clinician. This manuscript addresses DRE and provides an overview of treatment options, medical, surgical, and dietary. It addresses treatment strategies in polytherapy, then focuses on the role cenobamate (CNB) may play in reducing the burden of DRE while providing practical advice for its introduction. CNB is a recently approved, third generation, anti‐seizure medication (ASM), a tetrazole‐derived carbamate, thought to have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…However, since the study settings and the circumstances were similar, we still conclude that the high efficacy of CNB that was indicated by the pivotal trials 9,12 and confirmed by other real-world studies [18][19][20][23][24][25][26][27][28]35,38 was also obvious in our data.…”
Section: Comparisons Of Our Experiencessupporting
confidence: 87%
See 2 more Smart Citations
“…However, since the study settings and the circumstances were similar, we still conclude that the high efficacy of CNB that was indicated by the pivotal trials 9,12 and confirmed by other real-world studies [18][19][20][23][24][25][26][27][28]35,38 was also obvious in our data.…”
Section: Comparisons Of Our Experiencessupporting
confidence: 87%
“…Several expert recommendations proposed how to deal with such tolerability issues, especially considering pharmacokinetic and pharmacodynamic interactions with concomitant ASMs such as CLB, LTG, PHT, PB, OXC, or LCM. 34 , 35 , 36 , 37 , 38 Our study was initiated immediately after the introduction of CNB to the free market following the conclusion of the compassionate use program offered by the manufacturer in Germany. It is worth noting that we did not adhere to certain recommendations, such as proactive reductions of baseline ASMs under certain clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the pivotal trials and the published real-world evidence, it has been claimed that combinations of cenobamate with sodium-channel-blocking agents (for pharmacodynamic reasons) or with clobazam (for pharmacokinetic reasons) are associated with a higher risk of AEs [32]. We could not confirm this assumption from our data because these AEs were more common under combinations with levetiracetam and lamotrigine, although the plasma level of the latter usually drops under the influence of cenobamate [5,11,15,16].…”
Section: Discussionmentioning
confidence: 60%
“…From the pivotal trials and the published real-world evidence, it has been claimed that combinations of cenobamate with sodium-channel-blocking agents (for pharmacodynamic reasons) or with clobazam (for pharmacokinetic reasons) are associated with a higher risk of adverse events [33,34]. We could not confirm this assumption from our data because these adverse events were more common under combinations with levetiracetam and lamotrigine, although the plasma level of the latter usually drops under the influence of cenobamate [5,11,15,16].…”
Section: Discussionmentioning
confidence: 99%